Akuntabilitas Pengelolaan Dana Desa Di Desa Umbulsari, Kabupaten Jember - Devi Ardiani; Dedy Wijaya Kusuma; Nanda Widaninggar (STIE Mandala Jember, 2021)
This research was conducted to describe and study the Village Fund Management Accountability System from the planning, implementation and accountability stages. This research uses a qualitative exploratory method through a case study approach. This study uses interviews which are carried out in depth to each informant. The results of this study indicate that the implementation stage of the Village Fund in Umbulsari Village has implemented the principles of participation and transparency. For the implementation stage of village funds, the principles of participation, transparency and accountability have been implemented. Meanwhile, at the accountability stage, village funds have implemented the principle of accountability.